Owning Ethics: Corporate Logics, Silicon Valley, and the Institutionalization of Ethics - Metcalf, Jacob; Moss, Emanuel; boyd, danah (Social research, 2019)
In response to a cycle of ethical and political crises, Silicon Valley technology companies have begun placing significant resources into "ethics" initiatives, including assigning executive-level staff to coordinate product design practices and review policies across their organizations. These new "ethics owners" are tasked with responding to external challenges to the core logics of Silicon Valley that fuel its outsized power over individuals and society—meritocracy, technological solutionism, and market fundamentalism—by producing "ethics" practices that remain largely bounded by those logics. "Doing ethics" in tech companies consists of working through this tension.